COOPERATIVE TYPE NUMBER HEAD TOGETHER (NHT) WITH QUESTION CARD MEDIA IN LEARNING TENSES - Mohammad Arifin; Mohammad Labib Al Halim (FKIP, Universitas Billfath Lamongan, 2021)
This classroom action research was conducted at SMP Diniyah Al-Falahiyah Turi Lamongan for three months. This study aims to increase students' understanding of learning tenses using cooperative learning type Number Head Together (NHT) with question card media. The participants of this research were eighth grades students with a total of 20 students. The results of this study indicated that the implementation of Number Head Together (NHT) could increase students' understanding in learning tenses. The data obtained indicated that the set of learning targets have been achieved. Beginning from preliminary test, the students passed grades are 30%. Farther in cycle 1, the result increase to 55%. While in cycle 2, it could be said that the research target has been exceeded although there were still 15% students did not pass grades. Finally, in final test, it could be said that almost all the students passed grades with the percentage of 80%. Nevertheless, this research's target has been exceeded that 80% of students pass with an average value <70 with a minimum passing criterion of 67